Hits and (near) misses. Exploring managers' actions and their effects on localised resilience. Issue 3 (June 2020) - Turner, Neil; Kutsch, Elmar; Maylor, Harvey; Swart, Juani
Abstract: Resilience is clearly a desirable attribute, but characterising it is challenging, especially as it can be understood either as the response to an incident, or its successful avoidance. Individual- and organizational-level resilience are established fields of study, whereas mid-range, managerial-level, evidence of how 'localised' resilience (e.g. in the department, work unit or project) is achieved is lacking. We ask the question 'What do managers do to support resilience?' We report on a study carried out with senior staff from five major UK-based organizations. From our qualitative data investigating critical incidents and 'near-misses', we unpack the key (ongoing) actions that managers undertake, and show that these can be understood as a complex interweaving of exploitative and exploratory activities. We also identify five response archetypes utilised when an incident occurs. We show the simultaneity of multiple enabling and responding arrangements and, in so doing, uncover the 'messy' characteristics over time which enable the awareness and containment of potential and realised adversities, i.e. resilience.